Experimental Investigation of Strong-Field Ionization from Multiphoton to Tunneling Regimes Using Cross-Polarized Temporal Interferometry - Nie, Zan; Nambu, Noa; Marsh, Kenneth A.; Patchkovskii, Serguei; Morales, Felipe; Smirnova, Olga; Welch, Eric; Matteo, Daniel; Pigeon, Jeromy; Joshi, Chan (Optics InfoBase Conference Papers, 2022)
We have measured strong-field ionization yield versus laser intensity for various noble gases (Ar, Kr, Xe) and light polarizations from ultraviolet to near-infrared (267-800 nm), from multiphoton to tunneling regimes using cross-polarized temporal interferometry.
CRIS-Team Scopus Importer:2023-04-20